THU0289 PERSISTENCE OF CIRCULATING CRYOGLOBULINS AND RELATED SYMPTOMS AFTER HEPATITIS C VIRUS ERADICATION IN PATIENTS WITH MIXED CRYOGLOBULIN SYNDROME. (June 2019) - Bassoli, Cinzia Roberta; Oreni, Letizia; Sollima, Salvatore; Saccardo, Francesco; Sebastiani, Marco; Vacchi, Caterina; Mazzaro, Cesare; Zani, Roberta; Ferri, Clodoveo; Zignego, Anna Linda; Monti, Giuseppe; Brancaccio, Giuseppina; et al.
Abstract : Background: The powerful drugs with direct antiviral action (DAA) against hepatitis C virus (HCV) has made it possible to eliminate the trigger factor of Mixed Cryoglobulin Syndrome (MCS) and to extend the treatment to patients who could not tolerate IFN-based antiviral regimens. However, the persistence of cryoglobulin production and MCS-related symptoms despite SVR achievement is frequently reported. Objectives: The aim of this study was to assess the persistency rate of MCS-related clinical and laboratory indexes after successful treatment with DAA. Methods: CRESO (CRyoglobulinaemia Eradication Study Observational) is a multicentre observational study promoted by the Italian Society of Infectious and Tropical Diseases (SIMIT) and the Italian Group for the Study of Cryoglobulinaemias (GISC), aimed to assess the impact of DAA therapy on MCS symptoms and cryoglobulin production. Patients could be enrolled if they presented, during the 12 months before the enrolment, a cryocrit ≥0.5% and, at least, one episode of palpable purpura or, alternatively, arthralgia and fatigue with at least one symptom among peripheral neuropathy, Raynaud's phenomenon, lower limb ulcers or nephropathy, and a C4 level ≤8 mg/dL. Results: The present analysis was based on clinical and laboratory data of 94 patients (75.5% female with a median age of 67.5 years) that have been followed up for a median time of 24 weeks (IQR 12-24) after SVR12 achievement. At baseline the cryocrit was frankly positive in 85 (90.43%), detectable (>0.5%) in 4 and negative in 4 cases; patients with type II cryoglobulins and C4 levels ≤8 mg/dL were prevalent, respectively with 81.5% and 75.9%. Low eGFR values (≤45 mL/min/1.73m 2 ) were present in 12 cases (12.8%), 10 patients (10.6%) had a history of B-cell non-Hodgkin's lymphoma (NHL), and 1 of hepatocellular carcinoma, while liver cirrhosis was diagnosed in 22 cases (23.4%) and glomerulonephritis in 17 cases (18.1%). Patients were treated for 12 (72 cases) or 24 (21 cases) weeks with a total of ten different IFN-free DAA regimens. SVR12 was achieved in all 94 cases. Both prevalence and median cryocrit values decreased significantly after DAA treatment (p<0.0001), however, at the time of the last observation 56.4% of patients were still positive for MCs. The prevalence of purpura and fatigue significantly decreased (p<0.0001) as well sicca syndrome prevalence (p<0.015), while arthralgia and lower limb ulcers decrease did not reach statistical significance. In multivariate analysis, eGFR≤45 mL/min/1.73m 2 was an independent predictor of persistence of cryoglobulin production (AOR 7.7, CI 95% 1.6-37.2; p<0.011). Conclusion: CRESO study data confirm the persistence of cryoglobulin production and MCS symptoms in some patients, despite the eradication of HCV. This finding rises questions about the possible further evolution of the disease over time regardless the persistence of its original trigger. Disclosure of Interests: None declared